Daily time-use compositions of physical behaviours and its association with evaluative and experienced wellbeing: a multilevel compositional analysis - Anantha Narayanan; Scott Duncan; Conal Smith; Flora Le; Lisa Mackay; Julia McPhee; Basile Chaix; Tom Stewart (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background The composition of daily time-use physical behaviours—such as sedentary behaviour (SB), light physical activity (LPA), moderate-to-vigorous physical activity (MVPA), and sleep may be crucial for overall health and wellbeing. This study examined the associations between these time-use behaviours and both evaluative wellbeing (life satisfaction) and experienced wellbeing (momentary happiness, anxiousness, and tiredness). Evaluative wellbeing reflects an individual's overall life assessment, while experienced wellbeing captures real-time affective states. We investigated these associations by reallocating time among behaviours and assessing the predicted impact on wellbeing outcomes. Methods Time-use behaviours were obtained from 211 adults who wore Axivity AX3 accelerometers on their wrists for seven days. Participants also completed a survey to assess demographics and life satisfaction, before using a custom smartphone app to report their real-time happiness, anxiousness, and tiredness levels over seven days (at three random times each day). Time-use data were processed using UK Biobank machine learning algorithms. We employed Bayesian multilevel compositional analysis to investigate how time-use behaviours, and reallocating time between behaviours, were associated with both life satisfaction and momentary affective states. Results Increasing sedentary time (relative to other behaviours) over the week of observation was negatively associated with happiness and positively associated with anxiousness aggregated at the day level. Conversely, increasing the proportion of MVPA (relative to other behaviours) was associated with reduced anxiousness and tiredness. Substitution analysis showed that reallocating 20 min of SB to MVPA increased happiness by 0.12 units, 95% CI [0.01, 0.22] and reduced anxiousness by 0.20 units, 95% CI [-0.34, -0.07]. Additionally, reallocating 20 min of time spent in LPA to MVPA reduced tiredness by 0.16 units, 95% CI [-0.28, -0.03]. All affective states are reported on a 0–10 scale. No associations were found between time-use behaviours and life satisfaction. Conclusion Our study shows that time-use behaviours, particularly reducing sedentary time and increasing physical activity, were more strongly linked to experienced wellbeing. Studies that focus solely on examining time-use behaviours and long-term wellbeing outcomes, such as life satisfaction (common in population studies), may overlook the dynamic interplay and immediate impacts of behaviours on wellbeing. While some associations were present, most of the tested relationships were weak or non-significant, suggesting that contextual factors like social and environmental conditions may play a greater role in shaping wellbeing. The next step is to explore sequential associations, such as behaviours occurring immediately before or after a momentary affect response is recorded.